Self-expanding foam injected into the peritoneal space improves survival in a model of complex pelvic fracture and retroperitoneal exsanguination - David R King; Quynh P Pham; John O Hwabejire; Ahmed E Elsharkawy; Ahmed I Eid; Michael J Duggan; Shawn Gelsinger; Michael Fornaciari; Upma Sharma (Trauma Surgery & Acute Care Open)
Background Mortality for patients with pelvic fracture with hemorrhagic shock ranges from 21% to 57%. ResQFoam administered intra-abdominally has previously been shown to provide a survival benefit in large-animal models of abdominal exsanguination. It also significantly decreased mortality in models of retroperitoneal hemorrhage with complex pelvic fracture when deployed in the preperitoneal space. We hypothesized that percutaneously administered ResQFoam into the abdominal cavity could decrease mortality in exsanguinating pelvic hemorrhage.Methods Using non-coagulopathic Yorkshire swine, the injury model consisted of a unilateral, closed-cavity retroperitoneal vascular hemorrhage (with intraperitoneal communication) combined with a complex pelvic fracture. After the injury, animals received fluid resuscitation alone (control, n=14), fluid resuscitation with ResQFoam deployed in the preperitoneal pelvic space (n=10), or fluid resuscitation with ResQFoam deployed intra-abdominally (n=10). Hemodynamic monitoring was continued for 3 hours or until death.Results Intra-abdominal and preperitoneal use of ResQFoam provided a similar significant survival benefit compared with controls. The median survival times for the intra-abdominal and preperitoneal ResQFoam groups were 87 and 124 min, respectively, compared with 17 min for the control group (p=0.008 and 0.002, respectively). The survival rate at 3 hours was 40% for both ResQFoam groups compared with 0% in controls (p=0.020). There was no significant difference in the median survival time or overall survival curves between the two ResQFoam groups (p=0.734 and p=0.975, respectively). Both ResQFoam groups stabilized mean arterial pressure and significantly reduced hemorrhage rate. The average hemorrhage rate in control animals was 4.9±4.6 g/kg/min compared with 0.6±0.6 g/kg/min and 0.5±0.5 g/kg/min in the intra-abdominal (p=0.008) and preperitoneal (p=0.002) ResQFoam groups, respectively.Conclusions Similar survival benefit and hemorrhage control were achieved with ResQFoam in the treatment of exsanguinating pelvic hemorrhage with complex pelvic fracture whether it was administered preperitoneally or intra-abdominally. Thus, ResQFoam can be administered intra-abdominally to treat either abdominal or pelvic hemorrhage.Level of evidence Not applicable (animal study).